2012
DOI: 10.1063/1.3700729
|View full text |Cite
|
Sign up to set email alerts
|

Fast programming metal-gate Si quantum dot nonvolatile memory using green nanosecond laser spike annealing

Abstract: The ultrafast metal-gate silicon quantum-dot (Si-QD) nonvolatile memory (NVM) with program/ erase speed of 1 ls under low operating voltages of 6 7 V is achieved by thin tunneling oxide, in situ Si-QD-embedded dielectrics, and metal gate. Selective source/drain activation by green nanosecond laser spike annealing, due to metal-gate as light-blocking layer, responds to low thermal damage on gate structures and, therefore, suppresses re-crystallization/deformation/ diffusion of embedded Si-QDs. Accordingly, it g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 21 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Si nanocrystals (Si NCs) have been extensively studied in the past few years due to their potential applications in advanced nanoelectronic and optoelectronic devices, such as non-volatile memories 1 , light emitting devices 2 3 4 5 and the next generation of solar cells 6 7 8 . So far, most studies have been focused on the unintentionally doped Si NCs materials, and only a few works have been concerned with the impurity doping in Si NCs though it is a fundamental issue to develop the high performance Si NCs-based devices.…”
mentioning
confidence: 99%
“…Si nanocrystals (Si NCs) have been extensively studied in the past few years due to their potential applications in advanced nanoelectronic and optoelectronic devices, such as non-volatile memories 1 , light emitting devices 2 3 4 5 and the next generation of solar cells 6 7 8 . So far, most studies have been focused on the unintentionally doped Si NCs materials, and only a few works have been concerned with the impurity doping in Si NCs though it is a fundamental issue to develop the high performance Si NCs-based devices.…”
mentioning
confidence: 99%
“…Nanocrystalline Si (nc-Si) materials have been extensively studied because of their novel properties and their potential applications in future electronic and optoelectronic devices [ 1 , 2 ]. For example, the SiO 2 /nc-Si/SiO 2 sandwiched structures can be used as a floating gate to develop the non-volatile memories [ 3 ]. It has also been reported that nc-Si-based materials can be potentially used in light-emitting devices as well as next generation solar cells [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-crystalline Si (nc-Si) films have attracted much attention since they can be used in many kinds of devices such as Si-based light emitters, thin-film solar cells, as well as nonvolatile memories [ 1 , 2 , 3 , 4 , 5 , 6 ]. For example, highly efficient electroluminescence devices based on nc-Si have been fabricated and the external quantum efficiency reaches as high as 1.1% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%